Protection Scheme for MMC-MTDC Transmission Lines Based on Fault Coefficient - Dahai Zhang; Chuanjian Wu; Jinghan He; Pinghao Ni (CSEE Journal of Power and Energy Systems)
Multi-terminal direct current based on a modular multilevel converter (MMC-MTDC) has received more attention due to the advantages of large capacity and high flexibility. However, the current traveling wave protection schemes adopted by the MMC-MTDC DC project are not sufficiently sensitive to high-impedance faults. To solve this problem, this paper first analyzes the characteristics of the first traveling wave of the fault on the DC transmission line and derives the expressions of the first traveling wave of the fault when the DC transmission line has an internal and external fault. Subsequently, the line frequency characteristic is used to simplify the traveling wave expression and construct the fault coefficient. Finally, the principle of single-ended traveling wave protection based on the fault coefficient is proposed. Simulation results show that the protection principle has a strong ability to withstand transition resistance and noise interference.